Pengaruh Pengetahuan, Kesadaran, Dan Sanksi Perpajakan Terhadap Kepatuhan Wajib Pajak Orang Pribadi Karyawan Kota Tangerang - Nabilah Fitri; Moh. Taufan Nugroho; Viola Tashya Devana (UNIVERSITAS RAHARJA, 2023)
Tax is one of the domestic revenues used for national development. However, domestic revenues from taxes are not yet optimal. Domestic revenue is not optimal because the level of taxpayer compliance in carrying out tax obligations is still low. This study aims to determine the effect of tax knowledge, taxpayer awareness and tax sanctions simultaneously and partially on the Compliance of Individual Taxpayers in the City of Tangerang. The population in this study are individual employee taxpayers residing in the city of Tangerang. This study used non-probability sampling with a total sample of 131 people. The research data were analyzed using descriptive statistics and multiple linear regression analysis. The results of this study indicate that knowledge of taxation, awareness of taxpayers and tax sanctions simultaneously influence the compliance of individual taxpayers of Tangerang City employees. Partially, tax knowledge and taxpayer awareness have a positive effect on individual employee taxpayer compliance, while tax sanctions do not affect employee individual taxpayer compliance.